If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2) * x + 3 = 24 Reorder the terms: (2 + x) * x + 3 = 24 Reorder the terms for easier multiplication: x(2 + x) + 3 = 24 (2 * x + x * x) + 3 = 24 (2x + x2) + 3 = 24 Reorder the terms: 3 + 2x + x2 = 24 Solving 3 + 2x + x2 = 24 Solving for variable 'x'. Reorder the terms: 3 + -24 + 2x + x2 = 24 + -24 Combine like terms: 3 + -24 = -21 -21 + 2x + x2 = 24 + -24 Combine like terms: 24 + -24 = 0 -21 + 2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '21' to each side of the equation. -21 + 2x + 21 + x2 = 0 + 21 Reorder the terms: -21 + 21 + 2x + x2 = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 2x + x2 = 0 + 21 2x + x2 = 0 + 21 Combine like terms: 0 + 21 = 21 2x + x2 = 21 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = 21 + 1 Reorder the terms: 1 + 2x + x2 = 21 + 1 Combine like terms: 21 + 1 = 22 1 + 2x + x2 = 22 Factor a perfect square on the left side: (x + 1)(x + 1) = 22 Calculate the square root of the right side: 4.69041576 Break this problem into two subproblems by setting (x + 1) equal to 4.69041576 and -4.69041576.Subproblem 1
x + 1 = 4.69041576 Simplifying x + 1 = 4.69041576 Reorder the terms: 1 + x = 4.69041576 Solving 1 + x = 4.69041576 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 4.69041576 + -1 Combine like terms: 1 + -1 = 0 0 + x = 4.69041576 + -1 x = 4.69041576 + -1 Combine like terms: 4.69041576 + -1 = 3.69041576 x = 3.69041576 Simplifying x = 3.69041576Subproblem 2
x + 1 = -4.69041576 Simplifying x + 1 = -4.69041576 Reorder the terms: 1 + x = -4.69041576 Solving 1 + x = -4.69041576 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = -4.69041576 + -1 Combine like terms: 1 + -1 = 0 0 + x = -4.69041576 + -1 x = -4.69041576 + -1 Combine like terms: -4.69041576 + -1 = -5.69041576 x = -5.69041576 Simplifying x = -5.69041576Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.69041576, -5.69041576}
| 1/3-1/9x=-5/3 | | 2/11y+1/4=1/11y+8/5 | | 2ac-3bc-6bd+4ad=0 | | ac-3bc-6bd+4ad=0 | | (6x+8)(5x^2+9x+2)= | | x*x+7x+5=0 | | 5x^2+51x-360=0 | | -9p-7=10p | | x^4+2x^3=21-14x-4x^2 | | 9xy^4-xz^2=0 | | 2y^4=11y^2-12 | | f(5)=7(5)-22/4 | | Tan3.14/12 | | X+58=120 | | X-25=80 | | 9y-38=-8(y-8) | | (9x^2-5x-42)+(4x^2+7x)= | | -3x+5=-6x+14 | | (-3)+x=10 | | (2x+5)(6-3x)=0 | | 7x+4y+2z=1650 | | 6(x-2)=35 | | x^5-3*x^3=0 | | x^2+y^2+10x-14y+6=0 | | x*y=351 | | 6x+4y+3z=63 | | 3x+62=9x-10 | | px-qx=n | | Sec(x-pi/4) | | 0=-240 | | -4(2y+3)=-18 | | 16w^2-24w+9=0 |